STAND UP COMEDY SEBAGAI UPAYA PEMERTAHANAN BAHASA INDONESIA - Yudha Andana Prawira; Titim Kurnia (Tatar Pasundan: Jurnal Diklat Keagamaan, 2020)
Languages nowadays are on the way to its disappearance, with almost 50% of them in the process of extinction. The most effective to language preservation is by way using the media. Jurieen Survey (2016) elaborates that 61% of TV viewers fond of watching humor programs, one of which is stand up comedy. Hence, TV media is expected to contribute on language preservation, Bahasa Indonesia in particular. How significant the influence of stand up comedy and what aspects of comedy represent against language preservation are the two primary focuses on the research. Based on the data sources and analysis results, Four aspects of stand-up comedy cover: linguistic, social, economic and religious. The conclusion is stand up comedy can be an effective mean to preserve language and to educate the community. Stand up comedy would be easily accepted and digested by the community, due to its light and humorous presentation style.Keyword: language preservation; mass media; humor